Role of Managerial Ability on the Relationship between Sustainability Report and Tax Avoidance on Firm Value - Gunawan, Emylia Kusuma; Ng, Suwandi; Mardiana, Ana (Magister Akuntansi - Universitas Atma Jaya Makassar, 2024)
The purpose of the study is to investigate the effect of managerial ability sustainability report and tax avoidance on firm value. This research uses purposive sampling method in sample selection. The data sources in this study are annual reports and sustainability reports of non-financial companies listed on the Indonesia Stock Exchange for the period 2019 to 2021. Total of samples that met the criteria are 18 companies. The data collection method used is observation method. The study uses moderation regression analysis. The results show that sustainability report has a negative and no significant impact on firm value, tax avoidance has a positive and significant impact on firm value, managerial ability to strengthens the positive and significant influence between the sustainability report and firm value, managerial ability weakens the negative and no significant influence between the tax avoidance and firm value.